Joshua T. James, The Storied Ethics of the Thanksgiving Psalms - Pajunen, Mika S. (Journal of Semitic studies, 2020)
Mika Pajunen; Joshua T. James, The Storied Ethics of the Thanksgiving Psalms, Journal of Semitic Studies, Volume 65, Issue 1, 1 April 2020, Pages 257–259, http